2017
DOI: 10.1016/j.compositesb.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Full-scale testing and numerical analysis of a precast fibre reinforced self-compacting concrete slab pre-stressed with basalt fibre reinforced polymer bars

Abstract: Steel-free pre-stressed reinforced concrete may be used in aggressive environments to increase the durability of structural elements and to limit the carbon footprint by replacing steel with high-strength fibre composites. The design of a 10-m long steel-free precast fibre-reinforced concrete slab, pre-stressed with basalt-fibre reinforced polymer (BFRP) bars and shear-reinforced with glass-fibre reinforced polymer bars, is presented in this paper. Non-linear viscoelastic and elastic-plastic models have been e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This opened new opportunities for researchers and designers and allowed them to carry out realistic and improved modeling of FRP-strengthened concrete structures in which due consideration will be given to specifics related to adhesive/bonding agent as well as various failure mechanisms, including FRP debonding. As a result, recent studies employed modern simulation techniques to realize realistic modeling of FRP-related phenomenon [6,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This opened new opportunities for researchers and designers and allowed them to carry out realistic and improved modeling of FRP-strengthened concrete structures in which due consideration will be given to specifics related to adhesive/bonding agent as well as various failure mechanisms, including FRP debonding. As a result, recent studies employed modern simulation techniques to realize realistic modeling of FRP-related phenomenon [6,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence shows that prestressed BFRP reinforced elements have improved stiffness, approaching or surpassing that of steel reinforced elements with the same reinforcement ratio at levels of prestress over 30% of the ultimate tensile capacity of the bars. Due to the anisotropy of the mechanical properties of BFRP, the anchorage of tendons is also an area of high importance, especially for prestressing applications; issues such as slipping or crushing of the tendons have been reported when using industrial wedge anchorage (Dal Lago et al 2017;Motwani et al 2020) (Dal Lago et al 2017;Motwani et al 2020).…”
mentioning
confidence: 99%
“…Amin et al made materials characterisation of macro synthetic fibre reinforced concrete[157]. Dal Lago et al conducted full-scale testing and numerical analysis of a precast fibre reinforced self-compacting concrete slab pre-stressed with basalt fibre reinforced polymer bars[158]. Hamad aimed to find the size and shape effect of specimen on the compressive strenght of HPLWFC reinforced with glass fibres[159].Ahmad et al reported an experimental study on the properties of normal concrete, self-compacting concrete and glass fibre-reinforced self-compacting concrete[160].…”
mentioning
confidence: 99%